Cell sorting and germ layer formation in reconstructed starfish embryos. (28th September 2021) - Suzuki, Sohei; Omori, Ikuko; Kuraishi, Ritsu; Kaneko, Hiroyuki
Abstract: Germ layer formation is driven by embryonic cell sorting during the early developmental stages. Starfish ( Patiria pectinifera ) embryos have a connected endoderm and ectoderm, albeit with few contact surfaces between the epithelia. To better understand the association between cell sorting and germ layer formation, we reconstructed P. pectinifera embryos and examined their germ layer formation. Initial observations showed that the presumptive endodermal (pEN) and presumptive ectodermal (pEC) portions of the embryonic body at the late‐blastula stage were preserved throughout development. Based on this, cells that were dissociated from each dermal fragment were mixed in a reconstruction experiment. Our results showed that the pEN and pEC cells were located inside and outside the reaggregates, respectively, to form an embryonic body containing two epithelial layers, separated by a blastocoel. During this process, the pEN cells were motile and shifted from smaller clumps to form a large clump. In contrast, in reaggregates formed in separate cultures, the pEN cells showed strong adhesion abilities, whereas the pEC cells underwent epithelialization. Unlike that in pEN cells, the reaggregation of pEC cells preceded cadherin expression. Filamentous actin was similarly observed in both reaggregates. These results suggest that during the reconstruction of starfish embryos, germ layer formation occurs via the sorting of pEN and pEC cells, depending on their adhesiveness, motility, and epithelialization. In vivo, these properties might embody the physiological significance of cell adhesion in the germ layers constituting the epithelial monolayer. Abstract : Our results showed that presumptive endodermal (pEN) and presumptive ectodermal (pEC) portions of the embryonic body at the late‐blastula stage were preserved throughout development. In the main part of this article, we described identifications that the pEN and pEC cells had different adhesion, motility, and epithelialization properties, which enabled them to aggregate to their own kinds. Additionally, the differences in the adhesion, motility and epithelialization characteristics defined the shape and size of the pEN and pEC aggregates.